Hubungan Tingkat Pengetahuan Perawat tentang Identifikasi dalam Patient Safety dengan Pelaksanaannya di Ruang Rawat Inap RSUD SK. Lerik Kupang - Diyah Arini; Christina Yuliastuti; Rofina Lusia Jawa Ito (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2019)
Patient identification is a process for give a sign or identifier that includes the medical record number and patient identification with the purpose to make differences between another patients in order to accuracy of the provision services, the treatment and the implementation procedure to the patient. The purpose of this research was to determine The Relationship Level of Nurses Knowledge About Identification in Patient Safety with the Implementation at S. K Lerik Kupang inpatient hospital. Design an observational analytic study with cross sectional approach. The number of samples in this research from 64 nurses who were taken through simple random sampling technique. The results from of the study showed that 78.1%  had good enough knowledge and 21.9% had good knowledge. In its implementation 79,7% were good enough and 20,3% were good at carrying out patient safety identification. The Spearman rho test indicate that presence of relationship between the level of  nurses knowledge about identification in  patient safety with implementation, p = 0.001(p< a = 0.05). The conclusion from this research is the  nurses knowledge in the implementation of patient identification in pretty  good category. The results of this study can be input in order to more improve their knowledge through seminars and training about patient identification as well as apply the nurses knowledge in the implementation of patient identification.  Keywords : Knowledge, Identification in patient safety